Optimizing survival of large fibula osteocutaneous flaps for extensive full-thickness oromandibular defects: A two-stage approach with temporary orocutaneous fistula - SAÇAK, BÜLENT (My University, 2019)
Introduction: Composite and large head and neck defects requiring extensive skin-mucosa coverage are often reconstructed by combining flaps. Herein, we present a simple and reliable twostage fibula osteocutaneous (FOC) flap technique to improve the survival of a large skin paddle for oromandibular reconstructions. Methods: From October 2011 to September 2016, 47 patients with through-and-through oromandibular defects were reconstructed using FOC flaps with large skin paddles. To ensure optimum survival of skin paddles, temporary orocutaneous fistula were left in place and closed during the second stage operation via de-epithelialization of the skin paddle and suturing of mucosa. Demographic data, operative details, and postoperative complications were recorded. Results: The skin paddle dimensions ranged from 20 to 31.5 cm in length and 12 to 17 cm in width with an average area of 430.4 cm2 (range 300–504). The average time between the two stages and hospital stay were 10 days and 14 days, respectively. Complications at the donor site included wound dehiscence (n = 3, 6.4%), partial skin graft loss (n = 3, 6.4%) and hematoma (n = 2, 4.3%). Recipient site complications included two (4.3%) early postoperative venous congestions that resolved after elevation and three (6.4%) partial skin flap necrosis (less than 5% surface area). All complications resolved with bedside conservative management. There was only one take-back for evacuation of recipient site hematoma (2.1%) but no flap loss. Conclusion: Two-staged large skin paddle FOC flaps can simplify reconstruction of extensive oromandibular defects by improving the reliability of the sizable skin paddle and negating the need for a second flap.
Keywords: Tıp; Sağlık Bilimleri; Cerrahi Tıp Bilimleri; Medicine; Health Sciences; Surgery Medicine Sciences; CERRAHİ; Klinik Tıp; Klinik Tıp (MED); SURGERY; CLINICAL MEDICINE; Clinical Medicine (MED); Cerrahi; Surgery